2022
DOI: 10.1177/15280837211056986
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectrical properties of graphene knife-coated cellulosic fabrics for defect monitoring in Joule-heated textiles

Abstract: Knife-coating can confer new properties on different textile substrates efficiently by integrating various compounds into the coating paste. Graphene nanoplatelets (GNP) is one of the most used elements for the functionalization of fabrics in recent years, providing electrical and thermal conductivity to fabrics, later used to develop products such as sensors or heated garments. This paper reports thermoelectrically conductive textiles fabrication through knife-coating of cellulosic fabrics with a GNP load fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Graphene nanoplatelets (GNP) were applied to a cellulose fabric using the knife coating method, and the surface temperature of the resulting GNP-coated fabric increased to 100 °C within 60 s at an applied voltage of 40 V. The distribution of the surface temperature was affected by the uniformity of the GNP dispersion. The preparation of a well-dispersed conductive coating paste was highly important . Inspired by the polar bear pelt, Ag/cellulose/CNTs films with hydrophilicity, permeability, flexibility, and mechanical stability were fabricated using various methods, including knife-coated CNTs and magnetron-sputtering silver.…”
Section: Production Methodsmentioning
confidence: 99%
“…Graphene nanoplatelets (GNP) were applied to a cellulose fabric using the knife coating method, and the surface temperature of the resulting GNP-coated fabric increased to 100 °C within 60 s at an applied voltage of 40 V. The distribution of the surface temperature was affected by the uniformity of the GNP dispersion. The preparation of a well-dispersed conductive coating paste was highly important . Inspired by the polar bear pelt, Ag/cellulose/CNTs films with hydrophilicity, permeability, flexibility, and mechanical stability were fabricated using various methods, including knife-coated CNTs and magnetron-sputtering silver.…”
Section: Production Methodsmentioning
confidence: 99%
“…5(h)). 33,[56][57][58][59][60][61][62][63] The heater in this work exhibits high steady state temperature under low voltage, and also effective and rapid deicing capacity under 9 V voltage. At this moment, the input power density is only 0.146 W cm −2 , fully satisfying the practical demand of low-energy anti-icing and deicing.…”
Section: Electrothermal Performance and Electrothermal Deicing Applic...mentioning
confidence: 99%
“…By applying a voltage of 10 V, a steady-state temperature of 75.4 °C was achieved within 30 s for the fabricated Joule heater . In another study, conductive fabrics were created by applying graphene onto the textile substrate using a knife-coating technique . In this method, a coating paste consisting of a thickener, binder, fixing agent, ammonia, distilled water, and graphene nanoplatelets was prepared and then knife-coated onto the fabric samples.…”
Section: Introductionmentioning
confidence: 99%
“… 16 In another study, conductive fabrics were created by applying graphene onto the textile substrate using a knife-coating technique. 17 In this method, a coating paste consisting of a thickener, binder, fixing agent, ammonia, distilled water, and graphene nanoplatelets was prepared and then knife-coated onto the fabric samples. The study reported achieving temperatures of up to 100 °C under 40 V. Jain and Chatterjee developed graphene-functionalized fabrics for thermotherapy applications.…”
Section: Introductionmentioning
confidence: 99%